Determining the Effect of Afterglows in N2 Gas Mixtures for Sterilization - André Ricard; Cristina Canal; Sarah Cousty; Sandrine Villeger; Anne-Marie Pointu (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Chapter 25 compiles and summarizes the main findings of our earlier works investigating the correlations between the density of active species of N2 and N2-O2 afterglows and the characteristics of different treated surfaces for the sterilization of bacteria. The sterilizing properties of cold plasmas have been demonstrated in the last decades and have raised a wide interest. The employ of N2 microwave afterglows provide a mild platform for the sterilization of thermosensitive and delicate objects, and have allowed the transfer of this technology to the industry by the development of an industrial reactor. It is the aim of this work to compile and summarize the most relevant findings regarding this topic and provide the reader of the most suitable conditions for sterilization of contaminated material, and the outreach of this technique. In particular, the sterilization of E -coli bacteria by N2 microwave flowing afterglows was obtained at 5 Torr, 1slpm, 100w in a treatment time of 40 minutes by heating the bacteria holder at 60oC, and following this promising result, an industrial reactor (Plasmalyse) of 100 liters built by the Satelec company has allowed the sterilization of B-Stearo spores in 30 minutes at 80oC with N2 at 4 Torr, 1 slpm, 300 W. Testing a more complex configuration, the transmission of N -atoms through hollow tubes, interesting the sterilization of endoscopes, was obtained in polyamide tubes of int.dia. 1.5 mm and 50 cm length, by pulsing the plasma gas: pulse 1 s - period 2 s, pressure 0.9 - 2.3 Torr, Q = 1 slpm and 200 W: TN= 3.5%. When increasing the int.dia.to 3 mm and the length to 80 cm, the transmission of N -atoms was TN = 8.5% in the continuous discharge (4 Torr in the 5 liter reactor, 1 slpm and 150 W). It is deduced a destruction probability of the N-atoms on the tube wall: \(γ\)N = 1.610-3. With stainless tubes of int.dia. 1.5 mm and length 6.5 cm, it was obtained TN = 1.3% and \(γ\)N = 1.610-2.